1976
DOI: 10.1007/bf00508391
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of catecholamine release from the adrenal medulla by halothane

Abstract: In isolated bovine adrenals perfused with Locke solution in a retrograde fashion we investigated the effects of halothane on the catecholamine release evoked by various secretagogues. 1. The catecholamine release induced by activation of the nicotinic receptors on the chromaffin cells with 1,1-dimethyl-4-phenylpiperazinium was almost completely inhibited (by about 90%) by 1.4 X 10(-3) M halothane. 2. It was shown by means of cumulative concentration-response curves of acetylcholine for its stimulating effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…However, in the presence of excess calcium, each of the examined anesthetics inhibited exocytosis to some extent. These results are generally consistent with prior studies showing that volatile anesthetics inhibit secretory processes in intact cells (Pocock and Richards, 1986;Cheek et al, 1986;Sumikawa et al, 1985;Bosnjak et al, 1982;Gothert et al, 1976) and provide experimental support for our hypothesis that halothane inhibits the formation of the echinoderm fertilization envelope by impairing the Ca2+-regulated fusion of cortical vesicles with the egg plasma membrane (Hinkley and Wright, 1986). Although our 9-10) at 22 ° .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, in the presence of excess calcium, each of the examined anesthetics inhibited exocytosis to some extent. These results are generally consistent with prior studies showing that volatile anesthetics inhibit secretory processes in intact cells (Pocock and Richards, 1986;Cheek et al, 1986;Sumikawa et al, 1985;Bosnjak et al, 1982;Gothert et al, 1976) and provide experimental support for our hypothesis that halothane inhibits the formation of the echinoderm fertilization envelope by impairing the Ca2+-regulated fusion of cortical vesicles with the egg plasma membrane (Hinkley and Wright, 1986). Although our 9-10) at 22 ° .…”
Section: Discussionsupporting
confidence: 82%
“…These observations, in conjunction with the present data, suggest that exocytotic events in intact cells are more sensitive to anesthetics than those of isolated membrane (cortex) preparations. Supporting this notion, clinical concentrations of halothane have been reported to inhibit secretory events in intact chromaffin cells of the adrenal medulla (Pocock and Richards, 1986;Sumikawa et al, 1985;Gothert et al, 1976), mast cells in organ culture (Cheek at al., 1986), and explanted sympathetic ganglia (Bosnjak et al, 1982). A plausible explanation for the differences in anesthetic sensitivity observed between intact sea urchin eggs and isolated cortices is that volatile anesthetics may inhibit exocytosis by affecting some regulatory component or pathway (see below) which is partially inactivated or perhaps not well preserved in isolated cortices.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, volatile anaesthetics are known to inhibit catecholamine secretion from adrenal glands both in vivo and in vitro (Gothert et al, 1976;Gothert & Wendt, 1976). For these reasons, chromaffin cells offer a suitable experimental model for the analysis of the action of anaesthetics on neurosecretion.…”
Section: Introductionmentioning
confidence: 99%
“…Of the three ion channels in adrenal medullary cells general anaesthetics, such as enflurane (G6thert and Wendt 1977), ketamine (Takara et al 1986), halothane (G6thert et al 1976;Yashima et al 1986) and isoflurane , have been shown to inhibit most strongly the nicotinic acetylcholine receptor-associated ion channels. The order of potency of the inhibitory effect by these anaesthetics is: nicotinic actylcholine receptor-associated ion channels > voltage-dependent Na + channels >> voltage-dependent Ca 2 ÷ channels (Yashima et al 1986;Takara et al 1986.…”
Section: Comparison Of Propofol With Other General Anaesthetics On Iomentioning
confidence: 99%